The Effect of The Work Environment on Employee Performance in the Tandangsari Sumedang Multi-Bussiness Cooperative - Ading Rahman Sukmara; Sukmayadi Sukmayadi (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
This study aims to determine the influence of the work environment on employee performance at KSU Tandangsari Sumedang. The research method used in this study is a quantitative research method with data collection techniques used, namely, literature studies, interviews and questionnaires. The number of samples used in this study was 61 people. The data was analyzed using validity and reliability tests, descriptive statistics, normality tests, determination coefficients, simple linear regression analysis, and T tests. Based on the results of research on the work environment at KSU Tandangsari Sumedang, good results were obtained, this is in accordance with the total score obtained, which is 2,263 out of an ideal value of 3,050. Furthermore, the results of the research on employee performance also obtained good results, this was obtained from a total score of 2,415 out of an ideal value of 3,050. Then the correlation between the work environment and employee performance is very high, this is obtained from the value of the correlation coefficient (r) of 0.802 which is in the interval of 0.80-1.00. Meanwhile, based on the results of the T test, the hypothesis in this study was accepted, this shows that the work environment has a positive and significant effect on employee performance at KSU Tandangsari Sumedang. This result was obtained from a significance value of 0.00 with a ttable > calculation of 10.313 > 2.001 with an R square of 0.643, meaning that employee performance at KSU Tandangsari was influenced by 64.3% by the work environment and the remaining 15.7% was influenced by other factors that were not studied in this study.